53BP1 ablation rescues genomic instability in mice expressing 'RING‐less' BRCA1. (26th September 2016) - Li, Minxing; Cole, Francesca; Patel, Dharm S; Misenko, Sarah M; Her, Joonyoung; Malhowski, Amy; Alhamza, Ali; Zheng, Haiyan; Baer, Richard; Ludwig, Thomas; Jasin, Maria; Nussenzweig, André; et al.
Abstract: BRCA1 mutations strongly predispose affected individuals to breast and ovarian cancer, but the mechanism by which BRCA1 acts as a tumor suppressor is not fully understood. Homozygous deletion of exon 2 of the mouse Brca1 gene normally causes embryonic lethality, but we show that exon 2‐deleted alleles of Brca1 are expressed as a mutant isoform that lacks the N‐terminal RING domain. This "RING‐less" BRCA1 protein is stable and efficiently recruited to the sites of DNA damage. Surprisingly, robust RAD51 foci form in cells expressing RING‐less BRCA1 in response to DNA damage, but the cells nonetheless display the substantial genomic instability. Genomic instability can be rescued by the deletion of Trp53bp1, which encodes the DNA damage response factor 53BP1, and mice expressing RING‐less BRCA1 do not show an increased susceptibility to tumors in the absence of 53BP1. Genomic instability in cells expressing RING‐less BRCA1 correlates with the loss of BARD1 and a defect in restart of replication forks after hydroxyurea treatment, suggesting a role of BRCA1–BARD1 in genomic integrity that is independent of RAD51 loading. Synopsis: BRCA1 protein lacking the N‐terminal RING domain is stable and supports RAD51 focus formation at DSBs. Cells with "RING‐less" BRCA1 nonetheless show genomic instability, likely because of BARD1 loss and impaired stalled replication fork restart. Cells expressing a BRCA1 isoform lacking the RING domain show genomic instability, but can complete some steps of DNA repair that involve BRCA1 normally. The BRCA1 RING domain appears to be needed for restart of DNA replication following fork stalling. Ablation of 53BP1 can rescue most defects associated with loss of the BRCA1 RING domain. Abstract : BRCA1 protein lacking the N‐terminal RING domain is stable and supports RAD51 focus formation at DSBs. Cells with "RING‐less" BRCA1 nonetheless show genomic instability, likely because of BARD1 loss and impaired stalled replication fork restart.